(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The contribution, relying also on a narrative approach, offers some insights into the challenges that innovations in genetics and genomics daily present to the law. Recent progress in these areas has led to clear tensions over some of the categories and rights that traditionally populate the field of medicine. Although briefly, the work draws a renewed image of the person in the face of the changing contexts of research and medicine and suggests how this can be framed in the original declinations of constitutional principles, such as the centrality of the person, equality and solidarity.